Potential changes in cooling degree day under different global warming levels and shared socioeconomic pathways in West Africa. (28th February 2023) - Odou, Oluwarotimi Delano Thierry; Ursula, Heidi Heinrichs; Adamou, Rabani; Godjo, Thierry; Moussa, Mounkaila S
Abstract: Increasing levels of climatic warming are expected to affect the global development of energy consumption. The cooling degree day (CDD) is one of the climate-driven indices that captures the impact of climate on energy demand. However, little is known about the spatiotemporal trends of CDD in relation to a changing climate and economy in West Africa and its main implications. Hence, in order to analyze how energy demand could evolve, this study aims to assess the changes in CDD under 1.5, 2.0, 2.5, and 3.0 ° C global warming levels (GWLs), with and without population exposure and trends under the two representative concentration pathways (RCPs) of RCP4.5 and RCP8.5 for West Africa. A climate-reflective base temperature (T-base) is used and was determined using a piecewise linear regression method. Seasonal electricity consumption was derived using a decomposition feature. An ensemble of seven Global Climate Models (GCMs) were used for the future temperature projections. The future population was based on shared socioeconomic pathway outputs. Based on the analysis, the reported average T-base for the West African region is 24 ° C. An increasing CDD trend was identified in all of the RCP scenarios, but is more pronounced in RCP8.5. RCP8.5 departs from the mean historical period of approximately 20% by 2100 with the standardized value. The same trend is observed under different GWLs as the warming level increased and was most striking in the Sahelian zone. Population exposure to CDD (labelled CDDP) increases with warming levels, but is more pronounced in highly agglomerated areas. The CDDP index best captures the spatial representation of areas with high cooling demand potential with respect to the demographic distribution. This study can serve to inform better energy demand assessment scenarios and supply planning against the backdrop of changing climate conditions in West Africa.